Physical demands of elite basketball during an official U18 international tournament - Vázquez-Guerrero, J.; Jones, B.; Fernández-Valdés, B.; Moras, G.; Reche, X.; Sampaio, J. (Journal of Sports Sciences, 2019)
The aims of this study were (a) to compare players` physical demands between different playing positions in elite U18 basketball games and (b) to identify different clusters of performance. Data were collected from 94 male subjects (age: 17.4 ± 0.7 years), competing in a Euroleague Basketball Tournament. Guards covered a greater relative distance than centres and forwards (small to moderate effect). Forwards and guards had more peak accelerations, high accelerations and high decelerations than centres (moderate to large effects). A cluster analysis allowed to classify all cases into three different groups (Lower, Medium and Higher activity demands), containing 37.4%, 52.8% and 9.8% of the cases, respectively. The high accelerations, high decelerations, peak accelerations and total distance covered were the variables that most contributed to classify the players into the new groups. The percentage of cases distributed in the clusters according to playing position, game type (worst vs worst, mixed opposition, best vs best) and team were different. Centres have lower physical demands specially related with the number of accelerations and decelerations at high intensity and the peak acceleration when compared with guards. Each team has a different activity profile, that does not seem to influence the tournament outcome.